Algorithmic construction of the Postnikov tower for diagrams of simplicial sets - Filakovský, Marek; Čadek, Martin, 1957-; Masarykova univerzita. Ústav matematiky a statistiky (2016)
Hlavním cílem této práce je popis algoritmu, který pro konečný diagram jednoduše souvislých simpliciálních množin, zkonstruuje jeho n-patrovou Postnikovovu věž. Při použití Elmendorfovy věty je tento výsledek aplikovatelný i na algoritmické výpočty v ekvivariantní algebraické topologii. Dále uvádíme algoritmus, který pro dané simpliciální zobrazení mezi konečnými simpliciálními prostory rozhoduje, zda je toto homotopické s triviálním zobrazením.
The aim of the thesis is to provide an algorithm that given a finite diagram of simplicial sets, where all elements in the diagram are simply connected, constructs its n-stage Postnikov tower. The Elmendorf's theorem shows that this result is applicable to algorithmic computations in equivariant algebraic topology. Further, we present an algorithm that decides if a simplicial between finite simplicial sets is homotopic to a trivial map under the assumption that the target space is simply connected.
Vedoucí práce: Martin Čadek
Dizertace (Ph.D.)--Masarykova univerzita, Přírodovědecká fakulta, 2016
Keywords: algebraická topologie; algoritmy; algebraic topology; algorithms; disertace; dissertations